The sacT gene regulating the sacPA operon in Bacillus subtilis shares strong homology with transcriptional antiterminators. - Debarbouille, M (1990)
The expression of the Bacillus subtilis sacPA operon is induced by sucrose. A DNA fragment containing the upstream region of this operon was cloned. This fragment contains a promoter from which the operon is expressed. This upstream region also contains a palindromic DNA sequence very similar to the transcriptional terminator which regulates the induction of the B. subtilis sacB gene. Of 37 nucleotides in a region partially overlapping the sacP palindromic sequence, 34 were identical to the corresponding region of the sacB gene. A similar motif is also present in the bgl operon of Escherichia coli. The sacT locus controlling sacPA expression had been identified by a single constitutive mutation sacT30 which mapped close to the sacPA operon. DNA fragments containing the sacT+ and sacT30 alleles were cloned and sequenced. The sacT gene product is very similar to the B. subtilis sacY and to the E. coli bglG gene products. The constitutive sacT30 mutation was identified. It corresponds to a Asp-96-to-Tyr missense mutation located in a highly conserved region in SacT and SacY. These results strongly suggest that sacT is a specific regulatory gene of the sacPA operon.